THE CHANGES OF CLINICAL APPROACHES AND TACTICS OF TREATMENT IN ACUTE PANCREATITIS, TAKING INTO ACCOUNT THE REVIEWED ATLANTA 2012 CLASSIFICATION - V. І. Desyateryk; М. S. Кrykun (Клінічна хірургія, 2017)
THE CHANGES OF CLINICAL APPROACHES AND TACTICS OF TREATMENT IN ACUTE PANCREATITIS, TAKING INTO ACCOUNT THE REVIEWED ATLANTA 2012 CLASSIFICATION